Design and fabrication technique of thick-film circuits - Wagiran, Rahman; Yeop Majlis, Burhanuddin; Ramli, Abdul Rahman (1990)
This paper describes the stages in the design and fabrication of a hybrid circuit in thick-film technology. The material commonly used for thick-film circuit fabriation are also described. The use of CAD package greatly reduces the time required to develope the hybrid circuits.